The transformational and toxic leadership effect on employee retention - Justine Tanuwijaya; Jakaria Jakaria (Jurnal Manajemen dan Pemasaran Jasa, 2022)
One indicator of the success of a business process is employee retention and the factors that cause it include leadership style. This study was conducted with the aim of testing which one most dominantly affects employee retention, whether transformational leadership or toxic leadership mediated by job satisfaction. The research design used is hypothesis testing using the Structural Equation Model. Samples were taken by purposive sampling method to employees, both lecturers and academics staff in the scope of  Faculty of Economics and Business (FEB) Universitas Trisakti. The research findings showed that transformational leadership is proven to be more dominant in influencing employee retention than toxic leadership, either directly or indirectly through job satisfaction.Keywords:  employee retention; job satisfaction; toxic leadership; transformational leadership.